Stockholder-bondholder conflict and dividend constraints - Kalay, Avner (Journal of Financial Economics, 1982)
This paper examines a large, randomly chosen, sample of bond indentures focusing on the constraints they set on dividend payments that have the potential to transfer wealth from the bondholders (i.e., payments which are financed by a new debt issue or reduced investment). The nature of these restrictions support the hypothesis that bond convenants are structured to control the conflict of interest between stockholders and bondholders. Further, the empirical evidence suggests that these constraints are not binding — i.e., stockholders do not pay themselves as much dividends as they are allowed to. Explanations of this puzzling empirical regularity are suggested.